2021
DOI: 10.1186/s13054-021-03592-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of culture-negative and culture-positive sepsis or septic shock: a systematic review and meta-analysis

Abstract: Background Mortality and other clinical outcomes between culture-negative and culture-positive septic patients have been documented inconsistently and are very controversial. A systematic review and meta-analysis was performed to compare the clinical outcomes of culture-negative and culture-positive sepsis or septic shock. Methods We searched the PubMed, Cochrane and Embase databases for studies from inception to the 1st of January 2021. We include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
51
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 38 publications
7
51
1
1
Order By: Relevance
“…Nevertheless, beyond all these limitations, we fully agree with Li et al [ 1 ] that larger-scale studies are required to confirm or infirm their results.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, beyond all these limitations, we fully agree with Li et al [ 1 ] that larger-scale studies are required to confirm or infirm their results.…”
supporting
confidence: 87%
“…Recently in the Journal, Li et al [ 1 ] reported that culture positivity or negativity was not associated with differences in mortality, intensive care unit length of stay (LOS), mechanical ventilation requirements and renal replacement requirements of sepsis or septic shock patients. Conversely, hospital length of stay and mechanical ventilation duration of culture-positive septic patients were longer than those of culture-negative patients.…”
mentioning
confidence: 99%
“…The differences between these two groups are likely due to differences in patient populations, proportions of infection sites and resistance to antibiotics. 18 The long periods under mechanical ventilation, including under invasive ventilators and non-invasive ventilators, as well as the length of stay in the ICU, and the higher in-hospital mortality rate that was observed in the culture-positive patients were likely attributed to the greater occurrence of risk factors. These risk factors included patients being older, and having more severe infections, worse For personal use only.…”
mentioning
confidence: 99%
“…In addition, the clinical outcomes could be associated with the infection sources as well as the management of the sepsis patients. 18 Early comprehensive treatments, such as fluid resuscitation, appropriate use of antibiotics, nutritional support, and cleaning and care of infected sites, played a vital role in reducing mortality and improving clinical prognosis. Differently to culture-positive patients, the clinical prognosis of culture-negative patients was also not good despite their late mortality being lower.…”
mentioning
confidence: 99%
“…Recent studies have explored the association between culture positivity, a positive microbial culture of clinical samples during admission, and mortality in critically ill patients, but the evidence appeared to be inconclusive due to high heterogeneity among studies, with the majority of studies explored the short-term impact of culture positivity among patients with sepsis in the medical ICU [ 12 14 ]. Few studies, including our previous study focusing on 638 patients with cancer receiving perioperative intensive care, have found that culture positivity tended to be associated with 1-year mortality instead of short-term mortality [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%